2020
DOI: 10.1371/journal.ppat.1008776
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel AraC/XylS-regulated family of N-acyltransferases in pathogens of the order Enterobacterales

Abstract: Enteroaggregative Escherichia coli (EAEC) is a diarrheagenic pathotype associated with traveler's diarrhea, foodborne outbreaks and sporadic diarrhea in industrialized and developing countries. Regulation of virulence in EAEC is mediated by AggR and its negative regulator Aar. Together, they control the expression of at least 210 genes. On the other hand, we observed that about one third of Aar-regulated genes are related to metabolism and transport. In this study we show the AggR/Aar duo controls the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Although not directly tested in this work, based on similarities with Lnt, PE is likely the major source of palmitoyl for N-palmitoylation of CexE. In fact, Belmont-Monroy et al, 2020 suggested that PE is the major source of lipid due to an increase of PE in the aar mutant compared to the wild type. However, this seems counterintuitive as the deletion of aar results in an increase in aggR expression, which subsequently results in increased AatD production ( Morin et al, 2013 ; Santiago et al, 2014 ; Yasir et al, 2019 ); Aar is a negative regulator of aggR expression in EAEC 042 ( Santiago et al, 2014 ).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Although not directly tested in this work, based on similarities with Lnt, PE is likely the major source of palmitoyl for N-palmitoylation of CexE. In fact, Belmont-Monroy et al, 2020 suggested that PE is the major source of lipid due to an increase of PE in the aar mutant compared to the wild type. However, this seems counterintuitive as the deletion of aar results in an increase in aggR expression, which subsequently results in increased AatD production ( Morin et al, 2013 ; Santiago et al, 2014 ; Yasir et al, 2019 ); Aar is a negative regulator of aggR expression in EAEC 042 ( Santiago et al, 2014 ).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, N-palmitoylation of glycine appears to be a rare or under-described event and to our knowledge this is the first report of enzyme-mediated N-palmitoylation of a protein at a glycine residue. The recent publication by Belmont-Monroy et al, 2020 identified AatD as an acyltransferase of Aap and CexE responsible for N-palmitoylation of a glycine residue. However, this study failed to recognise this modification as the first confirmed example of enzyme-mediated N-palmitoylation of a glycine or to demonstrate that the position and conservation of the N-terminal amino acids were crucial to acylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations